Barriers to hepatitis B virus screening of pregnant women in primary healthcare centers in Nigeria: health workers’ perspective - Babayemi O. Olakunde; Daniel A. Adeyinka; Olubunmi A. Olakunde; Hasiya B. Raji; Hidayat B. Yahaya; Olugbengba A. Ijaodola; Clement O. Adesigbin (BMC Primary Care, 2023)
Abstract Background Hepatitis B virus (HBV) screening is an important component of antenatal care for pregnant women in Nigeria. However, the screening rates remain low, particularly at primary healthcare centers (PHCs). The objective of this study was to identify the barriers affecting antenatal HBV screening in PHCs in Nigeria from the perspective of health workers. Methods We conducted a survey among 30 health workers from 30 PHCs (one per PHC) across three states (Akwa Ibom, Anambra, and Kaduna) in Nigeria. An open-ended questionnaire was used to obtain written responses on the perceived barriers limiting antenatal HBV screening in PHCs and their recommended solutions to the identified barriers. The data were analyzed using an inductive thematic approach. Results The perceived barriers exist at patient, provider and health system levels. They included: lack of test kits, unaffordability of HBV test, shortage of trained personnel, poor awareness among pregnant women, knowledge of HBV among health workers, high cost of antiviral treatment, and unavailability of HBV vaccine. The recommended solutions to the identified barriers were: making test kits and vaccines available and free, creating awareness about HBV, and capacity-building interventions for health workers. Conclusions HBV screening of pregnant women attending PHCs in Nigeria appears to be affected by multilevel barriers. As the country continues to work towards eliminating HBV, these highlighted barriers at the patient, provider and health system levels must be addressed through effective and sustainable interventions.